2022
DOI: 10.3389/fmed.2022.913403
|View full text |Cite
|
Sign up to set email alerts
|

Veno-Arterial Extracorporeal Membrane Oxygenation in Elective High-Risk Percutaneous Coronary Interventions

Abstract: BackgroundThe safety and feasibility of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) as mechanical circulatory support in high-risk percutaneous coronary intervention (HR-PCI) remain unclear.MethodsThis retrospective study included patients with complex and high-risk coronary artery disease who underwent elective PCI with VA-ECMO support pre-operatively during March 2019–December 2020. Rates of VA-ECMO-related complications, complications during PCI, death, myocardial infarction, and stroke duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…eGFR pre-procedure were 67.22 ± 26.85 and post-procedure minimum 60.09 ± 27.78 (<0.002), Before PCI LVEF was 38.69 ± 13.65 and after PCI were 43.55 ± 13.72 (p<0.001) [3,4] In SYNTAX trials, results from ten years post-revascularization allcause mortality in PCI and CABG, no difference amongst both [2]. In this study HR-PCI triple vessels revascularization in CABG patients was successful but they were very limited in comparison to others in terms longer survival duration and no MACCE events post HR-PCI, Bai et al reported in their study, they formed a subgroup of patients underwent ECMO in elective HR-PCI that triple vessel in CABG patient survival rate was higher as compared to other PCI procedure but in left main stenosis PCI and CABG were same survival rate [21]. Revascularization stratagem in left main or triple vessel coronary artery disease patients were evaluated by cardiac surgeons/interventional cardiologists [2].…”
Section: Baseline Clinical Characteristicsmentioning
confidence: 60%
See 1 more Smart Citation
“…eGFR pre-procedure were 67.22 ± 26.85 and post-procedure minimum 60.09 ± 27.78 (<0.002), Before PCI LVEF was 38.69 ± 13.65 and after PCI were 43.55 ± 13.72 (p<0.001) [3,4] In SYNTAX trials, results from ten years post-revascularization allcause mortality in PCI and CABG, no difference amongst both [2]. In this study HR-PCI triple vessels revascularization in CABG patients was successful but they were very limited in comparison to others in terms longer survival duration and no MACCE events post HR-PCI, Bai et al reported in their study, they formed a subgroup of patients underwent ECMO in elective HR-PCI that triple vessel in CABG patient survival rate was higher as compared to other PCI procedure but in left main stenosis PCI and CABG were same survival rate [21]. Revascularization stratagem in left main or triple vessel coronary artery disease patients were evaluated by cardiac surgeons/interventional cardiologists [2].…”
Section: Baseline Clinical Characteristicsmentioning
confidence: 60%
“…This study outcomes aligns with similar studies conducted at other single-center facilities. [17][18][19][20][21][22][23]…”
mentioning
confidence: 99%
“…During PCI, ECMO does not depend on the patient’s heart rhythm and function, so it can provide a stable blood circulation and sufficient oxygen to the body and ischemic/hypoxic tissues, as well as reducing acidosis, promoting metabolite removal, promoting the recovery of the autonomic circulation, and reducing functional damage to other organs [ 4 ]. ECMO may pave the way for rapid myocardial reperfusion therapy, thereby reducing the mortality of critically ill patients with AMI and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In one study [22], among 2108715 consecutive patients with stable coronary artery disease undergoing elective PCI, 6905 (0.3%) patients underwent elective PCI with prophylactic mechanical circulatory support (MCS). The published experience with the IABP-SHOCK II trial suggested that IABP, an older circulatory assist device, was ineffective in patients with circulatory failure [23]. However, in clinical application, IABP will affect the operation process of intraaortic surgery because the counterpulsation balloon is placed in the descending aorta.…”
Section: Discussionmentioning
confidence: 99%